The Impacts of Fiscal Decentralization, Institutional Transformation, and Regional Revenue on Income Disparities between Provinces in Indonesia - Yohanes Maria Vianey Mudayen; Herry Maridjo (Universitas Hayam Wuruk Perbanas, 2017)
This study aims to determine the impacts of fiscal decentralization, institutional transformation, and regional revenue to the income disparity among the provinces in Indonesia. This study uses panel data with the number of runs 528 pieces of data that includes 33 provinces in Indonesia period 2000-2015. The data were taken from the Central Bureau of Statistics (BPS) and Bank Indonesia. They were analyzed using a multiple linear regression analysis. The results show that tax revenue sharing fund and natural resources revenue sharing fund impact positive and significant on the income disparity among the provinces in Indonesia, while the general allocation fund, special allocation fund, institutional transformation, and the local revenue do not significantly affect the income disparity among the provinces in Indonesia. Tax and natural resources revenue sharing fund are actually exacerbating the gap of income distribution among regions in Indonesia. The implication of this study is that the government needs to review the allocation mechanism of General Allocation Fund, Special Allocation Fund, Tax Revenue Sharing Fund and Natural Resources Revenue Sharing Fund in order to serve as an instrument of fiscal capacity equalization of each region as well income distribution equalization among regions in Indonesia. The local government needs to continue improving the local revenue through the optimization of local tax revenue, regional retribution, profits of Regional Owned Enterprises, and other legitimate acceptances.